EXPRESSION AND PURIFICATION OF N-ACYLHOMOSERINE LACTONASE IN EXTRACELULLAR FRACTION OF ESCHERICHIA COLI BL21(DE3) FROM AIIA GENE BACILLUS LICHENISFORMIS DAHB1 - Marco DJ, Martinus
Indonesia as one of the largest shrimp producers in the world can experience a drastic decline in shrimp production due to shrimp pathogens. One of emerging shrimp disease is Acute Hepatopancreatic Necrosis Disease (AHPND) was able to reduce shrimp production up to 45% in Thailand from 2012-2013. This disease is caused by Vibrio parahaemolyticus which utilizes the Quorum Sensing (QS) system to express virulence factors. One of prevention method that can be used to prevent the occurrence of QS in V. parahaemolyticus is Quorum Quenching (QQ) which aims to disrupt the QS signaling pathway by using enzymes or chemical compounds. One of the enzymes that can be used for this purpose is lactonase from the aiiA gene Bacillus licheniformis DAHB1 which hydrolyzes the lactone ring on N-acyl-homoserine lactone (AHL) so that AHL is degraded and disrupts the QS process. The aim of this study was to determine the expression of the AHL lactonase-producing aiiA gene in Escherichia coli BL21(DE3) in the extracellular area. In this study, the aiiA gene was inserted into the plasmid pET-26B(+) and transformed into Escherichia coli BL21(DE3). After that, the expression was carried out using various conditions of IPTG concentration (0, 0.5, 0.75, and 1 mM) and incubation time variations after IPTG induction (16, 20, and 38 hours) at 24?. The supernatant fraction (extracell) was analyzed using SDS-PAGE. The conditions that produced the highest protein yield were used for purification by Ni-NTA affinity chromatography column. The results of SDS-PAGE were analyzed using ImageJ and statistical significance was performed using One Way ANOVA and Post-Hoc using Tukey HSD. From the research, the constructs pET26b(+)-aiiA-6xHis and pET-26b(+)-N20-aiiA-6xHis have been successfully inserted and transformed in E. coli BL21(DE3) cells with confirmed PCR and colony PCR. Based on the results of SDS-Page, bands are suspected to be aiiA and N20-aiiA proteins. The highest yield of the extracellular fraction was found in incubation conditions after 16 hours of induction and there was a significance between treatments (p < 0.05) while for the IPTG variation there was no significance when compared to other treatment conditions (p > 0.05) so the IPTG concentration was chosen 0 ,5 mm. Protein isolates from the supernatant fraction with optimum conditions were then purified with a Ni-NTA column and the protein bands suspected to be aiiA and N20-aiiA were soluble by SDS-PAGE analysis. It is hoped that the pure isolates of aiiA and N20-aiiA can potentially be used for QS-based disease prevention in shrimp.